Analisa pengaruh temperatur pemanasan pada proses normalizing dan hardening quenching terhadap kekuatan tarik dan struktur mikro baut ST-60 - Sutrisno, Sutrisno; Azmal, Azmal; Handoko, Dwi (Universitas Muhammadiyah Metro, 2021)
This study aims to obtain information about the price of tensile, hardening, and changes in microstructure as well as changes in material properties at hot temperature variations 800 OC to 900 OC. The method used in this study is an experimental method, where the material used is ST-60 steel bolts, with a tensile test sample form referring to the ASTM D 638-03 standard, while for testing hardness and chemical composition based on machine standards, namely Ø16 mm x 20 mm. In this study, 5 samples were made at each temperature of 0 0C, 800 0C, 850 0C, 900 0C, 950 0C and 1000 0C with the type of heat treatment in the normalizing process and the hardening quenching process. This research was conducted in the Laboratorium Pengujian Bahan, Jurusan Teknik Mesin, Politeknik Negeri Pontianak. The test results on the normalizing process for tensile strength decreased by an average of 230.78 N/mm2 or 50%, Vickers hardness decreased by an average of 33.99 HV or 31% and the carbon content decreased by an average of 0.19 or 48% of the normalizing process is not done. Whereas in the hardening quenching process, the average tensile strength increased by 93.22 N/mm2 or 20 %, the Vickers hardness on average increased by 19.29 HV or 18 % and the average carbon content increased by 0.06 or up 17 % of the hardening quenching process was not done. So to overcome the decrease in mechanical strength and changes in the microstructure of the ST-60 bolt due to hot temperatures, the hardening quenching process can be applied, namely by polishing with used oil after the bolts work at hot temperatures.